1995
DOI: 10.1159/000171522
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drug-Induced Gastric Damage: Epidemiology

Abstract: Although figures vary considerably, the ingestion of aspirin or other non-aspirin non-steroidal anti-inflammatory drugs is associated with an increased risk of gastric ulceration, ulcer bleeding, ulcer complications and of death by a factor of around 3. Evidence for duodenal ulcer (DU) disease is less convincing, but the risk of complications of DU disease, bleeding and perforation, are increased to much the same extent as for gastric ulcer. Whether this increase in complications for DU represents exacerbation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…This undermines previous arguments that the effects of NSAIDs in duodenal ulcer disease are simply to exacerbate previous ulceration. 38 As in previous studies, 39 treatment was overall more likely to be successful for duodenal ulcers than gastric ulcers, and also with multiple erosions as the only lesion. However, healing of erosions was less likely to be successful if high doses of NSAIDs were used.…”
Section: Discussionsupporting
confidence: 52%
“…This undermines previous arguments that the effects of NSAIDs in duodenal ulcer disease are simply to exacerbate previous ulceration. 38 As in previous studies, 39 treatment was overall more likely to be successful for duodenal ulcers than gastric ulcers, and also with multiple erosions as the only lesion. However, healing of erosions was less likely to be successful if high doses of NSAIDs were used.…”
Section: Discussionsupporting
confidence: 52%
“…The use of NSAIDs also significantly increases the risk.32-34 It is estimated that the risk of a peptic ulcer is 2 4 % per year for patients taking NSAIDs, compared with a risk of 1-2% per year in the general p~p u l a t i o n .~~ Unknown amounts of overthe-counter NSAIDs are purchased annually, and approximately 100 million prescriptions for the agents are written each year in the United state^.^^^^^ Approximately one-half of these prescriptions are for patients older than 60 years, paralleling the age-related prevalence of arthritis.37-38 Numerous investigators identified a positive correlation between NSAID use, rates of gastrointestinal bleeding, and age ( Figure 2). 343 [39][40][41][42][43] In addition, consumption of NSAIDs, either alone or in combination with an anticoagulant, corticosteroid, or histaminez-receptor antagonist (HzRA), increases the risks of serious bleeding from ulcers, perforation, and mortality in elderly patients with a history of acid-related disease^. '^^^^ Several other exogenous and endogenous factors are implicated as risk factors, such as cigarette smoking and age-related changes in gastrointestinal defensive mechanisms.…”
Section: Risk Factorsmentioning
confidence: 99%